CHEMOTHERAPEUTIC POTENTIAL OF NOVEL XANTHONE SOURCED FROM SWERTIA CHIRATA AGAINST SKIN CARCINOGENESIS - BARUA, ATISH; CHOUDHURY, PRITHA; PANDA, CHINMAY KUMAR; SAHA, PROSENJIT (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Swertia chirata forms a rich source of bio-active compounds, among which xanthones form an important part. Among the xanthones present in it, 1,5,8 Tri-hydroxy-3-methoxy xanthone (TMX) was found to be the most active. The present study aims to evaluate the chemotherapeutic potential of it against metastatic skin cancer cell lines. Methods: In this study, the antitumor activity of TMX (the active component of chirata plant) was evaluated in A431, SKMEL-5, and A375 cell line by using in-vitro assays such as cell viability assay, cell cycle analysis, caspase 3 activity assay, intracellular reactive oxygen species (ROS) level determination by dichlorofluorescein diacetate, and quantitative real-time polymerase chain reaction (qRT-PCR). Results: In vitro studies showed that TMX from S. chirata exhibited significant antitumor activity by inducing apoptosis and restricting proliferation in both melanoma and non-melanoma skin cancer cell lines, but no such activity was seen in normal skin cancer cell line WS1. The qRT-PCR analysis revealed that in both the melanoma ad non-melanoma cell lines, TMX could exert its antitumor activity by downregulating c-Myc, cyclin-D1, and β-catenin and up-regulating Wnt antagonist gsk-3β, thereby suppressing wnt self-renewal pathway, but such regulation was absent in normal cell line. Conclusions: TMX from chirata could effectively inhibit the proliferation of metastatic skin cancer (both melanoma and non-melanoma) cell lines while being non-toxic to normal cell lines. The chemotherapeutic potential of TMX against metastatic skin cancer cell lines was achieved by downregulating several key regulatory genes enabling the suppression of the self-renewal pathway, the chief reason behind the invasiveness of cancer cells.